BDNF Levels and Cognitive Function in Patients with Type 2 Diabetes Treated with SGLT2 Inhibitors - Betül SÜMBÜL ŞEKERCİ; Şeymanur DEMİRHAN; Esra ÇALIŞICI; Abdüsselam ŞEKERCİ (Bezmiâlem Science)
Objective: As cognitive impairment becoming more widely recognized as a complication of type 2 diabetes mellitus (T2DM), it is discussed in the literature that antihyperglycemic treatment may also improve cognitive functions. Clinical research on this topic is particularly limited regarding sodium-glucose-cotransporter-2 (SGLT2) inhibitors. Brain-derived neurotrophic factor (BDNF) is a protein essential for cognitive functions and glucose metabolism. The aim of our research was to examine cognitive performance and BDNF levels in users of SGLT2 inhibitors. Methods: This cross-sectional study was conducted with 86 patients with T2DM, including 41 patients using metformin and 45 patients using SGLT2 inhibitors. Patients’ cognitive performance was assessed with the Montreal cognitive assessment (MoCA) test, and their serum BDNF levels were measured using the ELISA method. Results: There were no significant differences between SGLT2 inhibitor users and metformin users in MoCA total scores, as well as in the Visuospatial/Executive, Naming, Attention, Language, Abstraction, Memory, and Orientation subdomains. Although BDNF levels were relatively higher in the SGLT2 inhibitor group, the difference was not statistically significant. Significant correlations were observed between BDNF levels and the levels of microalbumin, microalbumin/creatinine, estimated glomerular filtration rate (eGFR), lymphocytes, According to linear regression analysis, effect of eGFR levels in predicting BDNF levels was significant. Conclusion: Our results indicated that cognitive performance and BDNF levels were similar between users of metformin and SGLT2 inhibitors. Clinical research investigating the effect of SGLT2 inhibitors on cognitive functions in T2DM is limited. Future prospective follow-up studies with SGLT2 inhibitors may provide more comprehensive information.